Residual Infusion Performance Evaluation (RIPE): A Single-Center Evaluation of Residual Volume Post-Intravenous Eravacycline Infusion - Alysa J. Baumann; Kerry O. Cleveland; Michael S. Gelfand; Nicholson B. Perkins III; Angela D. Covington; Athena L. V. Hobbs (MDPI AG, 2023)
Intravenous (IV) drugs are administered through infusion pumps and IV administration sets for patients who are seen in healthcare settings. There are multiple areas of the medication administration process that can influence the amount of a drug a patient receives. For example, IV administration sets that deliver a drug from an infusion bag to a patient vary in terms of length and bore. In addition, fluid manufacturers report that the total acceptable volume range for a 250 mL bag of normal saline can be anywhere from 265 to 285 mL. At the institution chosen for our study, each 50 mg vial of eravacycline is reconstituted using 5 mL of diluent, and the total dose is administered as a 250 mL admixture. This single-center, retrospective, quasi-experimental study evaluated the residual medication volume after the completion of an IV eravacycline infusion in patients admitted during the pre-intervention study period compared to those in the post-intervention study period. The primary outcome of the study was to compare the residual antibiotic volume remaining in the bags following IV infusions of eravacycline before and after the implementation of interventions. The secondary outcomes included the following: comparing the amount of the drug lost in the pre- and post-intervention periods, determining whether the amount of residual volume was affected by nursing shifts (day versus night), and lastly assessing the cost of facility drug waste. On average, approximately 15% of the total bag volume was not infused during the pre-intervention period, which was reduced to less than 5% in the post-intervention period. Clinically, the average estimated amount of eravacycline discarded decreased from 13.5 mg to 4.7 mg in the pre- and post-intervention periods, respectively. Following the statistically significant results of this study, the interventions were expanded at this facility to include all admixed antimicrobials. Further studies are needed to determine the potential clinical impact when patients do not receive complete antibiotic infusions.